ChemInform Abstract: Decarboxylative Allylation of Trifluoroethyl Sulfones and Approach to Difluoromethyl Compounds. Issue 11 (8th March 2013) - Shibata, Norio; Fukushi, Kazunobu; Furukawa, Tatsuya; Suzuki, Satoru; Tokunaga, Etsuko; Cahard, Dominique
Abstract Pd‐catalyzed coupling of trifluoroethyl sulfones with allyl carbonates allows an efficient access to fluorinated homoallyl sulfones like (III), (V), (VI), and (XI).